2012
DOI: 10.3390/ijms13033782
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the X-ray Diffraction Power of Protein Crystals by Dehydration: The Case of Bovine Serum Albumin and a Survey of Literature Data

Abstract: Serum albumin is one of the most widely studied proteins. It is the most abundant protein in plasma with a typical concentration of 5 g/100 mL and the principal transporter of fatty acids in plasma. While the crystal structures of human serum albumin (HSA) free and in complex with fatty acids, hemin, and local anesthetics have been characterized, no crystallographic models are available on bovine serum albumin (BSA), presumably because of the poor diffraction power of existing hexagonal BSA crystals. Here, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 92 publications
0
36
0
Order By: Relevance
“…Several studies have reported on the utility of controlled dehydration for improvement of the diffraction properties of protein crystals, and investigated how protein molecules reorganized to form improved packing contacts (Deng et al, 2012; Heras and Martin, 2005; Russo Krauss et al, 2012). Using a similar approach, we have previously found that brief soaking in a high osmolarity solution of crystals of the glmS ribozyme-riboswitch improved their diffraction limit (Klein and Ferré-D’Amaré, 2009; Klein et al, 2007) from 3.0 Å to 1.7 Å.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the utility of controlled dehydration for improvement of the diffraction properties of protein crystals, and investigated how protein molecules reorganized to form improved packing contacts (Deng et al, 2012; Heras and Martin, 2005; Russo Krauss et al, 2012). Using a similar approach, we have previously found that brief soaking in a high osmolarity solution of crystals of the glmS ribozyme-riboswitch improved their diffraction limit (Klein and Ferré-D’Amaré, 2009; Klein et al, 2007) from 3.0 Å to 1.7 Å.…”
Section: Discussionmentioning
confidence: 99%
“…Post-crystallization methods are more crucial for large proteins and macromolecular complexes since a new, and possibly better diffracting, crystal form is usually more difficult to obtain compared to small protein targets. The most used post-crystallization methods for improvement of the diffraction properties include soaking, cross-linking, annealing [261,262] and controlled dehydration [263,264]. Soaking of protein crystals with their product analogs, inhibitors, or strong ligands can be used to stabilize protein conformation and increase the crystalline lattice regularity.…”
Section: Improvement Of Crystallizability and Of X-ray Diffractiomentioning
confidence: 99%
“…In the fortunate cases, this procedure induces an internal rearrangement of the crystal that results in a significantly improved quality of the diffraction data. The various techniques for dehydrating crystals and the proteins whose diffraction pattern was improved through this procedure have been summarized in a recent paper [263]. To assure the control and reproducibility of dehydration, a number of dedicated devices have been produced [267270], some of which monitor in real time the X-ray diffraction pattern of the crystal [271–273].…”
Section: Improvement Of Crystallizability and Of X-ray Diffractiomentioning
confidence: 99%
“…This methodology can yield improved low-temperature crystalline order, 17 higher resolution of X-ray diffraction, 18 and reduced mosaicity.…”
mentioning
confidence: 98%